Adverse maternal and birth outcomes in women admitted to hospital for hyperemesis gravidarum: A population-based cohort study - Fiaschi, Linda; Nelson-Piercy, Catherine; Gibson, Jack E.; Szatkowski, Lisa; Tata, Laila J. (Wiley, 2017)
Background: Evidence for risks of adverse maternal and birth outcomes in women with hyperemesis gravidarum (HG) is predominantly from small studies, unknown, or conflicting.